CREATING KNOWLEDGE ABOUT ISLAM OF THE KAZAKH STEPPE: THE STEPPE, THE EMPIRE, AND THE OUTSIDER - Baiseit, Dina (Nazarbayev University School of Sciences and Humanities, 2022)
Thesis: The depiction of Islam that the Qazaqs practiced during the 19th and early 20th centuries differed hugely in the accounts of the outsiders and insiders. The first group, which included colonizers and foreigners, had specific purposes while creating accounts of this religion. One of the primary aims was, as Edward Said puts it, to justify their colonial presence in the region and oppressive policies toward these nomads. They depicted the Qazaqs as backward, uncivilized, and uneducated subjects who did not believe truly in Islam and were not true Muslims1 . Christian missionaries were present in the steppe and tried to convert the locals into Christianity. They believed blindly that they could convert the locals to Christianity, but after a couple of attempts failed and the tsarist government just decided to use Islam as a tool to control the locals by sending Tatar Muslims to the steppe and assigning them into positions of the steppe religious community before 1868. In 1868, Qazaqs were excluded from the Orenburg Spiritual Assembly.
Keywords: Type of access: Open Access; Islam; Kazakh steppe